Scalable ITIL Adoption Strategies for SMEs in Developing Countries: A Systematic Literature Review - Effendy, Faried; Nuqoba, Barry; Taufik, Taufik; Werdiningsih, Indah; Muhammadun, Muhammadun (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Small and Medium Enterprises (SMEs) play a vital role in the economic development of developing countries. As these businesses increasingly adopt digital technologies, structured IT service management becomes essential. The Information Technology Infrastructure Library (ITIL) provides a globally recognized framework for managing IT services, yet its application in SMEs remains limited due to resource constraints and operational differences. This study presents a systematic literature review to examine how ITIL has been implemented in SMEs across developing countries. From an initial collection of 100 publications, 20 relevant articles were selected for detailed analysis. The findings reveal diverse implementation strategies, with SMEs often adopting ITIL partially through selected processes such as incident or configuration management. Common barriers include lack of infrastructure, limited skilled personnel, and funding constraints. Despite these challenges, the review identifies critical success factors, including organizational awareness, leadership support, and contextual adaptation of ITIL practices. This study contributes structured insights for enhancing IT service management in resource-constrained SMEs and proposes strategic entry points for scalable adoption. The results offer practical guidance for decision-makers, IT managers, and policymakers, while also establishing a foundation for future empirical studies in SME-driven IT service governance.